RATS-Kepler - a deep high-cadence survey of the Kepler field - Gavin Ramsay; Adam Brooks; Pasi Hakala; Thomas Barclay; David Garcia-Alvarez; Victoria Antoci; Sandra Greiss; Martin Still; Danny Steeghs; Boris Gänsicke; Mark Reynolds (Oxford Journals, 2022)
We outline the purpose, strategy and first results of a deep, high-cadence, photometric survey of the Kepler field using the Isaac Newton Telescope on La Palma and the MDM 1.3 m Telescope on Kitt Peak. Our goal was to identify sources located in the Kepler field of view which are variable on a time-scale of a few minutes to 1 h. The astrophysically most-interesting sources would then have been candidates for observation using Kepler using 1 min sampling. Our survey covered ˜42 per cent of the Kepler field of view, and we have obtained light curves for 7.1 × 105 objects in the range 13 < g < 20. We have discovered more than 100 variable sources which have passed our two stage identification process. As a service to the wider community, we make our data products and cleaned CCD images available to download. We obtained Kepler data of 18 sources which we found to be variable using our survey, and we give an overview of the currently available data here. These sources include a pulsating DA white dwarf, 11 delta Sct stars which have dominant pulsation periods in the range 24 min to 2.35 h, three contact binaries, and a cataclysmic variable (V363 Lyr). One of the delta Sct stars is in a contact binary.